Investigating the Effects of Sedative and Antidepressant Drugs (Diazepam, Sertraline, and Their Combination) on Behavioral and Biochemical Changes in Zebrafish (Danio rerio) as an Animal Model - Shahab Tirgar Fakheri; Reza Changizi; Hamed Manoochehri; Ali Siahposht-Khachaki; Meysam Rameshgar (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Depression is one of the mental illnesses that affects a significant number of people. The zebrafish model has been proposed as a new tool for research on depression and other neurological disorders. The aim of this study was to investigate various aspects of the effects of antidepressant drugs, expand the scope of information derived from the Unpredictable Chronic Stress (UCS) protocol, and enhance understanding of the characteristics of zebrafish. Materials and methods: In this experimental study, a total of 384 adult short-finned zebrafish housed in 24 aquariums were used. The zebrafish were divided into two main groups: a control group (without stressors) and the UCS group. Within each group, the fish were further divided into four subgroups: control, diazepam (120 μg/L), sertraline (10 μg/L), and a combination of diazepam+ sertraline. Behavioral tests were conducted using the Novel Tank Test. Fish movements were recorded for six minutes and analyzed using EthoVision software. Biochemical tests were performed by measuring cortisol levels. Results: When the two drugs were used in combination, a significant decrease in the total distance traveled (from 37 to 18 meters), a significant increase in the time spent at the surface of the tank (from 55 to 154 seconds), and a significant increase in the number of trips to the surface (from 18 to 85 trips) were observed. Diazepam and sertraline also significantly reduced cortisol levels, from 1 ng/g tissue to 0.64 ng/g tissue and from 1 ng/g tissue to 0.15 ng/g tissue, respectively. Conclusion: This study reinforces the use of zebrafish as a model organism for investigating the behavioral and physiological effects of stress. Furthermore, the findings demonstrate that the combination of sertraline and diazepam may be effective in mitigating the progression of depression.